ANALISIS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA EKOLEA KECAMATAN WEWARIA KABUPATEN ENDE TAHUN 2018 DAN 2019 - Ida Rachmawati3, Getriana Luruk Bria Titin Ruliana 2 (EKONOMIA, 2021)
ABSTRACT The objectives to be achieved in this study are: 1.) To find out and analyze the management of APBDes in Ekolea Village, Wewaria District, Ende Regency in 2018 and 2019, it is not good in terms of the analysis of spending variance; 2.) To find out and analyze APBDes Management in Ekolea Village, Wewaria District, Ende Regency in 2018 and 2019 it is less balanced seen from the analysis of operating expenditures; 3.) To find out and analyze the management of APBDes in Ekolea Village, Wewaria District, Ende Regency in 2018 and 2019 it is less balanced seen from the analysis of capital expenditures; and 4.) To find out and analyze the management of APBDes in Ekolea Village, Wewaria District, Ende Regency in 2018 and 2019 it is less efficient, seen from the analysis of spending efficiency.The theoretical basis used is a theoretical basis concerning public sector accounting, Village Revenue and Expenditure Budget Management and budget reports.The analytical tool used is the expenditure analysis consisting of: expenditure variance analysis, operating expenditure harmony analysis, capital expenditure balance analysis and spending efficiency ratio.The research results put forward are: 1.) The expenditure budget in the 2018 and 2019 fiscal years seen from the analysis of the variance of expenditure in Ekolea Village, Wewaria District, is considered to be less good, so the first hypothesis is accepted; 2.) The expenditure budget in the 2018 fiscal year seen from the analysis of the harmony of operating expenditures in the Ekolea Village, Wewaria District is considered balanced, with a proportion category that is between 60-90%, so that the second hypothesis is rejected, while in the 2019 fiscal year it is considered less balanced with a less proportionate category from 60-90%, so that the second hypothesis is accepted; 3.) The expenditure budget in the 2018 and 2019 fiscal years, seen from the analysis of the compatibility of capital expenditures in Ekolea Village, Wewaria District, is considered unbalanced, with a proportion category that is between 5-20%, so that the third hypothesis is accepted; and 4.) The expenditure budget in the 2018 and 2019 fiscal years, seen from the efficiency ratio of spending in Ekolea Village, Wewaria District, is considered efficient, with an assessment category of less than 100%, so the fourth hypothesis is rejected.